2014
DOI: 10.6017/ital.v33i4.5273
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Current Awareness Service Using Yahoo! Pipes and LibGuides

Abstract: Migration from print to electronic journals brought an end to traditional current awareness services, which primarily used print routing. The emergence of Real Simple Syndication, or RSS feeds, and email alerting systems provided users with alternative services. To assist users with adopting these technologies, a service utilizing aggregate feeds to the library's electronic journal content was created and made available through LibGuides. Libraries can reestablish current awareness services using existing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Maull, Saldivar and Sumner (2012) explain that for a library to grow, it is necessary to adapt efficient and scalable methods to improve patronage. In this regard, Kiscaden (2014) evaluates the current information environment with its many available information sources and recognises that it may be difficult to keep abreast of current information sources relating to a specific discipline. To satisfy patrons' information requirements, librarians might need to determine patrons' ability to access, organise, use, and search for information (Aderibigbe & Emmanuel, 2012).…”
Section: Improving Satisfaction Among Library Patronsmentioning
confidence: 99%
“…Maull, Saldivar and Sumner (2012) explain that for a library to grow, it is necessary to adapt efficient and scalable methods to improve patronage. In this regard, Kiscaden (2014) evaluates the current information environment with its many available information sources and recognises that it may be difficult to keep abreast of current information sources relating to a specific discipline. To satisfy patrons' information requirements, librarians might need to determine patrons' ability to access, organise, use, and search for information (Aderibigbe & Emmanuel, 2012).…”
Section: Improving Satisfaction Among Library Patronsmentioning
confidence: 99%
“…eTOCs and RSS feeds both available from publishers' Web sites or subscription agents, provide notification when a new issue of a journal is made available. Making eTOCs or RSS feeds freely available to staff requires serious consideration of the target audience, suitable content, and end user familiarity and while librarians are enthusiastic about RSS feeds, and aware of their potential benefits lack of end-user knowledge can remain an impediment to uptake (5,6,8). DeGroote and Shultz's 2014 study found that few faculty members at their institution used social media technology, such as RSS, Twitter feeds, or read blogs or wikis in their field, with 84% indicating they had 'never' used these services (7).…”
Section: Introductionmentioning
confidence: 99%